A SEMANTIC COGNITIVE ANALYSIS OF IDIOMS IN BATAK TOBA WEDDING CEREMONIES - Tiarnita Maria Sarjani Siregar; Adel Pinola Br Ginting, Deviara Lestari, M. Rafif Zaki Ramadhan, Nurfarah (International Journal of Teaching and Learning, 2024)
This research delves into the semantic cognitive analysis of idioms in Batak Toba wedding ceremonies, examining the customary terms and their meanings in the pre-wedding, wedding ceremony, and post-wedding stages. Drawing from previous studies and employing qualitative methods, the study classifies the terminology based on process, actors, and cultural objects. It analyzes these terms' lexical, grammatical, and cultural meanings, highlighting their significance in Batak Toba culture. The study reveals the intricate layers of meaning embedded in these customary terms and underscores their importance in understanding the rich cultural heritage of the Batak Toba people. The research explores how these idioms bridge literal and figurative meanings through a cognitive semantics lens, reflecting the community's values and beliefs. The findings contribute to the broader discourse on cultural semantics and enrich our understanding of Batak Toba wedding ceremonies' linguistic and cultural intricacies.